Concept of Humanism in Shah Abdul Latif’s Bhattai Poetry - Buriro, Hakim Ali; Saeed, Saima; Latif, Wasif (sourcecoder, 2023)
This research aims to study the Sindhi mystical poet Shah Abdul Latif bhattai poetry through the lenses of humanism. He composed his poetry for every single common man to inculcate the message of love, unity, brother hood and solidarity through using Sindhi language .His poetry provoke the positive traits toward human being and tried to eradicate hater, prejudices and socially constructed stigma in society.He spread the message of humanism irrespectively by colour,cast and creed.Being a Sufi saint he tried to denounced the extravagance, injustice and exploitation at all levels, and preached simplicity and peace. His mystic poetry and spiritual approach carries a message of affection and universality of the human race.